Modelling the Legacies of War Violence: Voters, Parties, Communities - Josip Glaurdić; Christophe Lesschaeve; Michal Mochtak (Anali Hrvatskog Politološkog Društva, 2018)
Wars are extreme events with profound social consequences. Political science, however, has a limited grasp of their impact on the nature and content of political competition which follows in their wake. That is partly the case due to a lack of conceptual clarity when it comes to capturing the effects of war with reliable data. This article systematises and evaluates the attempts at modelling the consequences of war in political science research which relies on quantitative methods. Our discussion is organised around three levels of analysis: individual level of voters, institutional level of political parties, and the aggregate level of communities. We devote particular attention to modelling the legacies of the most recent wars in Southeast Europe, and we offer our view of which efforts have the best potential to help set the foundations of a promising research programme.